Manfaat Penggunaan Teknologi Informasi Di Sekolah Menengah Atas Dalam Proses Pembelajaran - Elena Dementieva Lase; Hetty Yakin Nauli Lase (CV. SINAR HOWUHOWU, 2024)
The use of information technology in learning at the Senior High School (SMA) level has become a crucial aspect in today's digital era. This study discusses the main benefits of technology implementation, including more structured lesson planning, more efficient administration, and broader access to educational resources. With planning software, educational managers can design annual plans and effectively monitor student progress, providing timely feedback. Digitalization also simplifies the management of student data, attendance, and reporting, reducing the burden of manual work. Improved access to digital learning materials enriches the learning experience for both students and teachers. Student motivation in using information technology is highly influential, as their understanding of technology’s benefits can increase interest and engagement in learning. This study aims to explore the challenges and opportunities in the implementation of information technology in schools and provide recommendations to enhance learning effectiveness in the future.